Molecular biological studies on neuropeptides of the adipokinetic hormone/red pigment-concentrating hormone family and the neuroparsin family in the arthropod sister groups of insects and crustaceans - Anders, Lance (Department of Biological Sciences, 2014)
Includes abstract.